The Social Genome Model: Estimating How Policies Affect Outcomes, Mobility and Inequality across the Life Course. (December 2016) - Acs, Gregory; Martin, Steven; Schwabish, Jonathan A.; Sawhill, Isabel V.
Abstract : Persistently high poverty among families with children, a lack of equal opportunity, stalled intergenerational mobility, and inequality have all risen up the agenda for federal, state, and local policymakers. Children born into low‐income families face barriers to success in each stage of life from birth till age 40. Using data on a representative group of American children and a life cycle model to track their progress from the earliest years through school and beyond, we show that well‐evaluated, targeted interventions can close over 80% of the gap between more and less advantaged children in the proportion that ends up middle class by middle age. These interventions can also greatly improve social mobility and enhance the lifetime incomes of less advantaged children.